Antialcoholic propaganda as essential part of the formation of health life in the beginning of XX century: historic and pedagogical analyses - Lukjanchenko M.I (Kharkov National Pedagogical University, 2010)
Operations on struggle against harmful habits are analyzed. Then public problems are made out, is specified on the reasons of their rise. Historical and social conditions of rise of a problem formation of a healthy way of life are made out. It is specified on malign influence of alcohol on development of a young organism. It is noted, that the rising generation does not own a sufficient level of knowledge of ways of conservation and strengthening of health. It is exhibited, that formation of skills of a healthy way of life is influenced with activity of the person: his rushing to reach an object in view, to realize own ambitions or desires. Practical references on formation of skills of a healthy way of life of rising generation are detected.